At loggerheads over state aid: Why the Commission rejects aid and governments comply. (September 2020) - Finke, Daniel
State aid is of significant importance to EU economies. The Commission is responsible for monitoring that all aid instruments comply with EU law. The present article analyses two questions: Why does the Commission reject aid instruments? How do national governments respond to such rejections? I argue that national governments are more willing to risk conflict with the Commission if perceived corruption and Euroscepticism are high. The Commission anticipates the likelihood of non-compliance when ruling on proposed aid instruments. If it expects non-compliance, the Commission is more likely to reject an aid instrument where its public trust ratings are high. If non-compliance is unlikely, the Commission can focus exclusively on the legal consistency of its ruling. On the empirical side, I test my arguments by analysing all state aid decisions between 2000 and 2018. Most importantly, the results show that state aid is more likely to be rejected, where public trust in the Commission is high.